Digital signal processing for CdZnTe semiconductor detectors based on cubic spline smoothing function. (20th November 2009) - Shaaban, Noha
The purpose of this paper is to present a theoretical analysis of B-spline signal representation from a signal processing point of view. The noise component included in the measured signal waveform greatly affects the result of numerical signal waveform processing. In order to suppress the harmful influence by the noise, we have investigated the smooth waveform data priori to the numerical analysis. Spline function can be used to obtain not only a smooth interpolation curve for given data points but also a smoothed curve for them. The smoothed signal rise time and the improved energy spectrum of a planar CdZnTe semiconductor detector were introduced in order to show the effectiveness of the method.